A review of Rhopalopsole magnicerca group (Plecoptera: Leuctridae) from China - Li, Weihai; Yang, Ding (Zootaxa, 2012)
The species of Rhopalopsole magnicerca group (Plecoptera: Leuctridae) from China are reviewed. Two additional species of the group are described as new: R. minutospina sp. nov. and R. wolong sp. nov. Rhopalopsole longispina and R. xui are considered as additional members of the group. The taxonomic relationships of new species with congeners are discussed and a key for the Chinese species in the group is presented.